포스트 코로나 시대, 일대일로 프로젝트의 실상과 한일의 전략적 협력 방안 - 한동균(Dong-Gyoon Han), 남호석(Ho-Seok Nam) (무역연구, 2020)
Purpose This study aims to investigate the possibility of participation and strategic cooperation of South Korea and Japan in the Belt and Road Initiative (BRI). As South Korea and Japan are geopolitically important countries for China sharing common interests in the fields of economy, diplomacy, and security, both countries can be strategic partners to establish a new economic cooperation model. Design/Methodology/Approach With the review of the purpose and the trend of the BRI until now, cases of cooperation between China and the BRI participating country were examined to understand the China’s influence of bilateral cooperation on the participating country. Based on that, the cooperation strategy of South Korea and Japan toward the BRI was investigated if each country has a strategy for harmonious cooperation with China in a context with the BRI. Findings It was found that there are common perceptions between South Korea and Japan toward the BRI. First, both countries recognize the importance of investigating on the China-centered economic cooperation system to be prepared for the uncertainties derived from the BRI. Next, Participation through public-private partnerships and multilateral banks can reach further effective cooperation. Lastly, deliberate action is highly required because of the deepened trade dispute between the US and China. Research Implications This study implicates the necessity of a practical approach for South Korea and Japan toward the BRI under the pressure from the US and China in the post-COVID-19. Considering the common perceptions, the potentiality of Korea-Japan cooperation can be expected to maximize the benefit by participating in the BRI. KCI Citation Count: 2